Cohort profile: the open, prospective Community-Based chronic Care Lesotho (ComBaCaL) cohort – design, baseline chronic disease risk factors and hypertension and diabetes care cascades - Matthias Briel; Thilo Burkard; Ravi Gupta; Frédérique Chammartin; Alain Amstutz; Thabo Ishmael Lejone; Eleonora Seelig; Irene Ayakaka; Mosa Tlahali; Matumaole Bane; Makhebe Khomolishoele; Tristan Lee; et al. (BMJ Open)
Purpose The open, prospective Community-Based chronic Care Lesotho (ComBaCaL) cohort is the first study to comprehensively investigate socioeconomic indicators, common chronic diseases and their risk factors in a remote rural setting in Lesotho. It serves as a platform for implementing nested trials using the Trials within Cohorts (TwiCs) design to assess community-based chronic care interventions. In this study, we present the cohort’s sociodemographic and chronic disease risk factor profile, including self-reported HIV prevalence and hypertension and diabetes care cascades.Participants Since February 2023, community health worker (CHWs) supported by a clinical decision support and data collection application have enrolled inhabitants from 103 randomly selected rural villages in Butha-Buthe and Mokhotlong districts in Northeast Lesotho. As of 31 May 2024, the cohort includes 5008 households with 14 735 participants (55% female, median age 19 years). The cohort’s socioeconomic status is low with an International Wealth Index of 26, a monthly household income of US$42.4 and low levels of formal education. Among the 7917 adult participants, 42.5% are overweight or obese, with higher rates among women, and 33.1% smoke tobacco, with higher rates among men. Self-reported HIV prevalence is 15.1% with a 98.4% treatment rate. Hypertension prevalence is 17% with a 56% control rate and diabetes prevalence is 4% with a 39% control rate.Findings to date The cohort’s low socioeconomic status is linked to multiple health risks including insufficient access to clean energy, essential healthcare services, adequate sanitary facilities and secure food supply. Besides the expected high HIV prevalence, we found significant hypertension, diabetes and cardiovascular risk factor prevalences. While treatment and control rates for diabetes and hypertension are higher than in similar settings, they remain below global targets.Future plans Ongoing cluster-randomised TwiCs, which will be completed in 2025, are assessing the effectiveness of community-based, CHW-led care interventions for diabetes and hypertension. CHWs will continue to closely monitor the cohort and integrate additional measurements such as HIV testing. This will provide further insights into the dynamics and interactions of chronic diseases and inform the development of future nested trials on innovative community-based prevention and care interventions.Trial registration number NCT05596773.